The Effect of Using a Language Games-Based Electronic Program on Acquiring Oral Expression Skills among People with Learning Difficulties in English Language during Covid-19 Pandemic - Mohamad Ahmad Saleem Khasawneh (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2021)
The purpose of this study was to identify the effect of using a language games-based electronic program on developing the oral expressions of people with learning difficulties in the English language during the emerging Covid-19 pandemic. The study used the experimental approach and implemented the program on a sample of 84 students, who were distributed to an experimental group (42) and a control group (42). The instruments of the study consisted of the training program and a test for the evaluation of oral expressive performance. The study found the existence of significant differences between the experimental and control groups in the acquisition of oral expression after receiving the training program in favor of the experimental group.